Yemen and the politics of permanent crisis - Phillips, Sarah (Adelphi (Series) (International Institute for Strategic Studies), 2011)
Summary : "The Middle East is in the midst of considerable and unpredictable changes, but deeply patrimonial political systems do not change overnight - and neither do the international and regional structures that have helped them to endure for so long. The informal rules that guide Yemeni society and its dysfunctional political settlement look set to endure, in spite of unprecedented protests. Entangled in a narrative of acute crisis and possible state failure, the country still relies on foreign assistance to prop up its ailing economy. Fearing the threat from al-Qaeda on Yemeni soil as well as the crisis of the Houthi insurgency and the southern secessionist movement, regional and Western powers have continued to bankroll the regime without taking significant steps to address the underlying causes of instability and threat."